2008
DOI: 10.1113/jphysiol.2008.159814
|View full text |Cite
|
Sign up to set email alerts
|

AMPK‐independent pathways regulate skeletal muscle fatty acid oxidation

Abstract: The activation of AMP-activated protein kinase (AMPK) and phosphorylation/inhibition of acetyl-CoA carboxylase 2 (ACC2) is believed to be the principal pathway regulating fatty acid oxidation. However, during exercise AMPK activity and ACC Ser-221 phosphorylation does not always correlate with rates of fatty acid oxidation. To address this issue we have investigated the requirement for skeletal muscle AMPK in controlling aminoimidazole-4-carboxymide-1-β-d-ribofuranoside (AICAR) and contraction-stimulated fatty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
114
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(141 citation statements)
references
References 62 publications
23
114
4
Order By: Relevance
“…Muscle AMPK activity and ACC phosphorylation In agreement with previous reports [33,40,41], α2AMPK activity was reduced in the gastrocnemius (~50%), soleus (~80%) and EDL (~95%) muscles from KD mice compared with wild-type (Fig. 1a,c).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Muscle AMPK activity and ACC phosphorylation In agreement with previous reports [33,40,41], α2AMPK activity was reduced in the gastrocnemius (~50%), soleus (~80%) and EDL (~95%) muscles from KD mice compared with wild-type (Fig. 1a,c).…”
Section: Resultssupporting
confidence: 92%
“…These findings are in agreement with previous studies [38,40,41] and suggest that residual α1AMPK activity is unable to compensate for the reduced α2AMPK activity when it comes to ACC phosphorylation. Surprisingly, this dramatic reduction in resting/basal ACC phosphorylation in KD mice did not result in greater accumulation of muscle lipids or increases in body mass, epididymal fat pad weight or serum leptin between high-fat fed KD and wild-type mice.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Moreover, beneficial effects of physical activity in obese and type 2 diabetic patients are associated with an increase in the oxidative capacity of skeletal muscle potentially through activation of AMPactivated protein kinase (AMPK) [13]. However, skeletal muscle fatty acid oxidation can be regulated independently of AMPK [14]. Moreover, the theory of mitochondrial dysfunction in type 2 diabetes has been refuted by other studies, which have shown that mitochondrial function was not altered in type 2 diabetes skeletal muscle after normalisation to mitochondrial content [15] or when control and type 2 diabetic participants were matched for body composition [16].…”
Section: Introductionmentioning
confidence: 99%